Pemahaman Masyarakat Tentang Pencemaran Udara terhadap Lingkungan Hidup di Kota Serang - Azmi Syafanah Nur Hasna; Ikhsan Gatot Aji Prasetio; Iik Nurul Fatimah; Euis Aprianti (Lembaga Pengembangan Kinerja Dosen, 2025)
Air pollution is an increasingly serious environmental issue in major cities, including Serang City. The decline in air quality due to motor vehicle emissions, industrial activities, waste incineration, and the reduction of green open spaces harms public health and the environment. Polluted air can cause respiratory problems, reduce the quality of life, and threaten urban ecosystems. This study aims to analyze the level of knowledge, perceptions, and behaviors of Serang City residents regarding air pollution, as well as assess their support for air pollution control policies. The methods used include a mixed-method approach through questionnaires, in-depth interviews, and participatory observation. The results of the study show that the community has a good understanding of the sources of air pollution, particularly vehicle and industrial emissions. They are also aware of the impact of pollution on health, especially for children and the elderly. However, the implementation of protective behaviors such as wearing masks is not yet consistent. Some positive behaviors have begun to develop, such as not burning trash and planting plants at home. Support for pollution control policies is also high. This study emphasizes the importance of continuous education, law enforcement, and collaboration between the government, society, and environmental communities in efforts to mitigate air pollution in Serang City.